The Care and Nurturing of Eastern Cottontail Rabbits (Sylvilagus floridanus) - King, Gail M. (Wildlife Rehabilitation Bulletin, 2007)
Many wildlife rehabilitators have complained about how difficult rabbits are to rehabilitate. Many have stated that young rabbits die for no apparent reason before they can be released. The emphasis of this paper is to address key issues wildlife rehabilitators face when rehabilitating young cottontail rabbits (bunnies). The author is confident that those who follow the guidance outlined will experience a high rehabilitation success rate with rabbits. In turn, they will experience the joy of releasing this wonderful mammal back into its natural habitat.